Blasser Schimmer - A pale gleam : Sammlung Mondstudio Collection. - von Bismarck, Beatrice; Federle, Helmut; Grcic, Konstantin; Grcic, Tamara; Hartel, Steffi; Marioni, Joseph; Meller, Ingo; Reed, David; Reul, Bernward; Schwenk, Bernhart; Seemann, Hellmut; Uglow, Alan; et al. (Köln : Gimlet Verlag, 2001)
Alighiero e Boetti ; Arad, Ron ; Baer, Monika ; Balka, Miroslaw ; Baumkötter, Stephan ; Bogin, Greg ; Brandl, Herbert ; Braun, Matti ; Calame, Ingrid ; Cole, Max ; Dadamaino ; Drescher, Jürgen ; Dumas, Marlene ; Exner, Andreas ; Falley, Nicola ; Federle, Helmut ; Förg, Gunther ; Francis, Mark ; Frize, Bernard ; Gormley, Antony ; Grcic, Tamara ; Grosse, Katharina ; Hamak, Herbert ; Hartel, Steffi ; Haynes, Nancy ; Hofmann, Kurt ; Hohenbüchler, Christine & Irene ; Höller, Stefan ; Horn, Roni ; Huws, Bethan ; Judd, Donald ; Katase, Kazuo ; Katz, Alex ; Kawara, On ; Klein, Yves ; Knoebel, Imi ; Koch, Udo ; Koons, Jeff ; Levine, Sherrie ; Linke, Simon ; Mangold, Robert ; Männikkö, Esko ; Marcaccio, Fabian ; Marden, Brice ; Marioni, Joseph ; McCaslin, Matthew ; Meller, Ingo ; Milroy, Lisa ; Mosset, Olivier ; Mundt, Wilhelm ; Noir ; Ostendarp, Carl ; Paesler, Susanne ; Panton, Verner ; Parrino, Steven ; Pitsou, Evangelia ; Reed, David ; Rehnberg, Hakan ; Reineking, James ; Richter, Gerhard ; Roeth, Winston ; Rosenthal, Stephen ; Ruscha, Edward ; Ryman, Robert ; Sander, Karin ; Schiess, Adrian ; Schulze, Andreas Karl ; Simpson, David ; Skreber, Dirk ; Slominski, Andreas ; Spalletti, Ettore ; Stockholder, Jessica ; Sugimoto Hiroshi ; Takeoka, Yuji ; Templin, Susa ; Thurzs, Frédéric Matys ; Toenges, Michael ; Tollens, Peter ; Trockel, Rosemarie ; Uglow, Alan ; Umberg, Günter ; Venezia, Michael ; Vital, Not ; Warhol, Andy ; Warmuth, Herbert ; Weizsäcker, Andreas von ; Wellmann, Ulrich ; Wesley, John ; Zandvliet, Robert ; Zaugg, Rémy ; Zeniuk, Jerry ; Zimmermann, Peter
Duits & Engels
boek